The road to effective tobacco control in China. Issue 9972 (14th March 2015) - Yang, Gonghuan; Wang, Yu; Wu, Yiqun; Yang, Jie; Wan, Xia
Summary: The non-communicable disease burden in China is enormous, with tobacco use a leading risk factor for the major non-communicable diseases. The prevalence of tobacco use in men is one of the highest in the world, with more than 300 million smokers and 740 million non-smokers exposed to second-hand smoke. In the past decade public awareness of the health hazards of tobacco use and exposure to second-hand smoke has grown, social customs and habits have changed, aggressive tactics used by the tobacco industry have been revealed, and serious tobacco control policies have been actively promoted. In 2014, national legislators in China began actively considering national bans on smoking in public and work places and tobacco advertising. However, tobacco control in China has remained particularly difficult because of interference by the tobacco industry. Changes to the interministerial coordinating mechanism for implementation of the WHO Framework Convention on Tobacco Control are now crucial. Progress towards a tobacco-free world will be dependent on more rapid action in China.